Does FDI affect migration flows? The role of human capital - D’AGOSTO, ELENA; SOLFERINO, NAZARIA; TRIA, GIOVANNI (Migration Letters, 2013)
Global trade and capital movements across countries are increasing along with significant international workers mobility. The aim of this paper is to analyse the link between FDI inflows and emigration waves across developing countries. We test the twofold direction that this link may follow, either through complementarity or substitution effects. By using a cross section analysis for the year 2000 with a sample including 91 developing countries, it is shown that both of them are at work While a strong positive relationship (complementarity) between migration flows and FDI arises, FDI may also be seen as a substitute for migration through direct and indirect labour demand effects. In particular, we find evidence that human capital is a channel for the substitutability effect.